Appendix Neuroendocrine Tumor: Retrospective Analysis of 4026 Appendectomy Patients in a Single Center. (3rd September 2020) - Bayhan, Zulfu; Yildiz, Yasin Alper; Akdeniz, Yesim; Gonullu, Emre; Altintoprak, Fatih; Mantoglu, Baris; Capoglu, Recayi; Kahyaoglu Akkaya, Zeynep
Abstract : Background/Aim. Appendix tumors are mostly incidentally identified in patients who were operated with the diagnosis of acute appendicitis. They are detected in approximately 1% of appendectomy specimens. Neuroendocrine tumors (NETs) account for over 50% of appendix neoplasms. NETs appearing in the appendix can cause carcinoid syndrome. In our study, we aimed to retrospectively examine the clinical features of patients who underwent appendectomy with the diagnosis of acute appendicitis and diagnosed with appendix NET in the postoperative period. Materials/Methods. The records of 4026 patients who were operated with the diagnosis of acute appendicitis between January 2008 and January 2020 at the Department of General Surgery at the Sakarya University Faculty of Medicine, were evaluated retrospectively. Clinical findings, demographic data, surgical findings, and results of the patients with appendix NET, as a result of histopathology, were examined in detail. Results . 16 of 4026 patients were reported as NET. Nine of the patients were male, and seven were female. The average age was 33 (19–49). Any of the patients had no signs and symptoms of carcinoid syndrome. All tumors were located at the tip of the appendix, and the mean tumor diameter was 0.85 cm (0.3–2.5 cm). As a result of pathology, one patient had mesoappendix and one patient had serosa invasion. Right hemicolectomy was applied to both patients. In other patients, meso, serosa, and lymphatic invasion were not detected. Tumor size was 2.5 cm in one of the patients, 1.5 cm in one, and 1.4 cm in the other, and the others were below 1 cm. In the postoperative follow-up, all the patients were discharged on average 2.71 (2–6 days) days without any complications. Conclusion. Appendix NETs are mostly asymptomatic and localized in a distal third of the appendix. Symptoms are mostly related to tumor size and distant metastases. Clinical behavior and prognosis can best be predicted by tumor size. Complementary hemicolectomy is recommended for tumors larger than 2 cm and tumors smaller than 1 to 2 cm, such as mesoappendix invasion, positive or uncertain surgical margin, high proliferative rate, and angioinvasion. For tumors whose diameter is less than 1 cm, simple appendectomy alone is sufficient.